Tumor necrosis factor-α/interleukin-10 balance in normal and cystic fibrosis children - Galina V. Shmarina; Alexander L. Pukhalsky; Svetlana N. Kokarovtseva; Daria A. Pukhalskaya; Lidia A. Shabalova; Nikolai I. Kapranov; Natalia J. Kashirskaja (Mediators of Inflammation)
Background: The balance between tumor necrosis factor-α (TNF-α) and interleukin-10 (IL-10) is important for immune homeostasis maintenance. Exuberant production of TNF-α contributes to overwhelming inflammatory response and tissue damage. But, commonly, increase in TNF-α is counterbalanced by simultaneous synthesis of an anti-inflammatory cytokine IL-10, which suppresses production of many activating and regulatory mediators.